PERKEMBANGAN RISET DISPOSISI MATEMATIS DALAM PEMBELAJARAN MATEMATIKA: SEBUAH SYSTEMATIC LITERATURE REVIEW (SLR) - Suryana, Andri; Nia Kurniasih, Enok; Wartini, Nani; Wintarsih, Ade; Juliana Soleh, Mega; Insani, Sri; Sumarni, Yunita; Hajar Birlanti, Shofina; Rusyanih, Yanih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematical disposition is an important affective aspect that influences students' success in mathematics learning. Numerous studies have examined mathematical disposition from various perspectives, including problem-solving ability, mathematical literacy, critical thinking, creative thinking, and learning achievement. However, these studies are still scattered across different publications, making it necessary to conduct a comprehensive review. This study aims to analyze the development of research on mathematical disposition in mathematics learning through a Systematic Literature Review (SLR) approach. The data consisted of 24 scientific articles published between 2016 and 2025. The articles were selected based on predetermined inclusion criteria and analyzed using descriptive qualitative techniques. The analysis focused on research methods, research trends, and the main findings related to mathematical disposition. The results indicate that quantitative research is the most frequently used method in studies of mathematical disposition. Furthermore, mathematical disposition has a positive relationship with various mathematical abilities, such as problem-solving, critical thinking, creative thinking, mathematical literacy, mathematical representation, conceptual understanding, and mathematics achievement. Several learning approaches, including Problem Based Learning (PBL), Realistic Mathematics Education (RME), and technology-assisted learning, were also found to contribute positively to the improvement of students' mathematical disposition. Therefore, mathematical disposition should be considered an essential aspect in mathematics learning to support students' academic achievement and higher-order thinking skills.